2023
DOI: 10.3390/jcm12155161
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Side Effects in Patients Treated with Immune Checkpoint Inhibitors: A Narrative Review

Nicia I. Profili,
Roberto Castelli,
Antonio Gidaro
et al.

Abstract: Checkpoint inhibitors are monoclonal antibodies that elicit an anti-tumor response by stimulating immune system. Their use has improved the treatment of different types of cancer such as melanoma, breast carcinoma, lung, stomach, colon, liver, renal cell carcinoma, and Hodgkin’s lymphoma, but several adverse events have been reported. Although the etiology of these effects is not completely understood, an uncontrolled activation of the immune system has been postulated. Indeed, some studies showed a cross reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 124 publications
0
5
1
Order By: Relevance
“…Conversely, our study found that the incidence of hypothyroidism following anti‐PD1 treatment was lower, ranging from 7.8% to 12.8% in a different type of gastrointestinal cancer. These findings are distinct from previous studies that observed a higher frequency of thyroid dysfunction in patients with antibodies targeting PD‐1 compared to CTLA‐4 inhibitors 16,17 . De Filette et al also found that nearly 20% of patients receiving anti‐PD‐1 antibodies experienced thyroid dysfunction in real‐world settings 18 .…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Conversely, our study found that the incidence of hypothyroidism following anti‐PD1 treatment was lower, ranging from 7.8% to 12.8% in a different type of gastrointestinal cancer. These findings are distinct from previous studies that observed a higher frequency of thyroid dysfunction in patients with antibodies targeting PD‐1 compared to CTLA‐4 inhibitors 16,17 . De Filette et al also found that nearly 20% of patients receiving anti‐PD‐1 antibodies experienced thyroid dysfunction in real‐world settings 18 .…”
Section: Discussioncontrasting
confidence: 90%
“…These findings are distinct from previous studies that observed a higher frequency of thyroid dysfunction in patients with antibodies targeting PD-1 compared to CTLA-4 inhibitors. 16,17 De Filette et al also found that nearly 20% of patients receiving anti-PD-1 antibodies experienced thyroid dysfunction in real-world settings. 18 These variations could be due to the larger sample size in our study and our division of thyroid dysfunction into hyperthyroidism and hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, all four patients experiencing CPI-DM received anti-PD-1 agents, and one of them was in combination with an anti-CTLA-4 agent. Indeed, recent data [20] have demonstrated that anti-PD-1 and anti-PD-L1 agents are more prone to trigger the onset of DM in comparison to anti-CTLA-4. Moreover, and in agreement with a systematic review by Wu et al [7], including 192 confirmed CPI-DM cases (the time of diagnosis: from 6 to 24 weeks after the onset of immunotherapy, with DKA in 69.7% of cases), the time of diagnosis in our small series ranged from 1 month to 1 year, while 2 of the 4 cases presented with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these patients had symptomatic hyperglycemia at onset, while 85% of them might complicate with ketosis. Concerning parathyroid involvement, hypoparathyroidism (and exceptionally primary hyperparathyroidism [ 198 ]) was diagnosed despite the fact that parathyroid tissue does not hold receptors for PD-1, PD-L1, or CTLA-4, but, probably, antibodies against the calcium-sensing receptor are drug-induced [ 199 , 200 , 201 ]…”
Section: Discussionmentioning
confidence: 99%